2015
DOI: 10.7448/ias.18.1.19843
|View full text |Cite
|
Sign up to set email alerts
|

Linkage to care following a home‐based HIV counselling and testing intervention in rural South Africa

Abstract: IntroductionEfforts to increase awareness of HIV status have led to growing interest in community-based models of HIV testing. Maximizing the benefits of such programmes requires timely linkage to care and treatment. Thus, an understanding of linkage and its potential barriers is imperative for scale-up.MethodsThis study was conducted in rural South Africa. HIV-positive clients (n=492) identified through home-based HIV counselling and testing (HBHCT) were followed up to assess linkage to care, defined as obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
123
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(139 citation statements)
references
References 35 publications
16
123
0
Order By: Relevance
“…These linkage-to-care results (49% at 3 months) are in line with other studies conducted in sub-Saharan Africa using home-based [26,27] and other testing strategies [6]. Our study adds to the evidence base that home-based testing strategies are effective to diagnose and link to care remaining undiagnosed individuals in a population where an already high proportion is diagnosed, but also underscores that more attention is needed to support timely linkage to care.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These linkage-to-care results (49% at 3 months) are in line with other studies conducted in sub-Saharan Africa using home-based [26,27] and other testing strategies [6]. Our study adds to the evidence base that home-based testing strategies are effective to diagnose and link to care remaining undiagnosed individuals in a population where an already high proportion is diagnosed, but also underscores that more attention is needed to support timely linkage to care.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to other studies, we found that young HIVpositive adolescents and young adults (age [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] were less likely to be diagnosed and to link to care once diagnosed. Survey data collected from sub-Saharan Africa indicate that only 10% of young men and 15% of young women (15-24 years) were aware of their HIV status [34].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The probability of linking to care was also higher in the first month than in subsequent periods. This has been observed previously 10, 38 and may mean that persons who accept their status, and are motivated to get help, promptly link to care following HIV diagnosis 41. The finding also suggests that one month after HIV diagnosis may be the optimal time for targeting persons who are less motivated to seek care.…”
Section: Discussionmentioning
confidence: 63%
“…Results from observational studies suggest that counselling provided after referral could increase linkage to care among HIV‐positive persons identified through HBHCT in SSA 6, 7, 8, 9, 10. A major limitation of observational studies, however, is that it is difficult to account for the effects of confounding factors.…”
Section: Introductionmentioning
confidence: 99%